Optimal Locational Choice for Agribusinesses in Madagascar : An Application of Spatial Autoregressive Tobit Regression - Iimi, Atsushi (World Bank, Washington, DC, 2018)
The traditional location theory predicts that firms' locational choice is independent of the output demand. However, firms are often concentrated in large markets. In Africa, agrobusinesses are expected to play an important role to facilitate agricultural growth but are hardly available in rural areas. This paper examines the question of why agribusinesses are not located in local production areas despite the clear benefits expected from close proximity to their inputs. By applying the spatial autocorrelation Tobit model, the paper estimates the impacts of market and farm accessibility on agglomeration of new agrobusinesses in Madagascar. The findings show that market accessibility and agglomeration economies are important for attracting more agrobusinesses. The quality of labor is also an important determinant for their locational choice. The findings are consistent with some models of location theory: firms move away from rural areas where they may still have monopsony power, toward urban areas where productivity is higher.